Mechanistic Study of Substituent Effect on Photoinduced O-C Bond Activation in Polycarbonate - Xiao Huang; Yuuichi Orimoto; Yuriko Aoki (Molecules)
Photodegradation of polycarbonate (PC) is investigated based on quantum chemical methods with PC models to clarify the effect of substituents at different positions of phenyl rings on the carbonate O-C bond cleavage. Compared to the results without substituents on phenyl rings, the breakage of the carbonate O-C bond is promoted or suppressed when the electron-donating or electron-withdrawing group is placed on the meta- or ortho-positions of the gem-dimethyl groups of phenyl rings, respectively. Moreover, the promotion and suppression of carbonate O-C bond scission are more significant if the substituents are located on the ortho-positions of the gem-dimethyl groups.